Multiscale warpage behaviour in a Fan-Out Panel during thermal cycles. (November 2022) - Hölck, O.; Vernhes, P.; Gamba, B.; Cruz, R.; Huber, S.; Braun, T.; Schneider-Ramelow, M.
Abstract: In this work, the warpage of a panel in the context of fan-out packaging is analysed. On a panel size of 300 × 300 mm 2 a die layout is molded and debonded from the temporary carrier. The resulting warpage is characterised temperature dependent using the Projection Moiré technique globally across the complete panel and locally on the scale of few dies. Globally, results are analysed with respect to the shape change of the warpage and residual warpage after thermal cycling. Locally the curvature of single dies is compared to the global curvature of the tunnel shaped warpage. This work is part of the investigations with the aim to describe and control the warpage effects in Fan-Out Panel Level Packaging. Highlights: Topography Deformation Measurement was used to characterise temperature dependent warpage. Changes of warpage shape from tunnel to cushion were observed to follow a hysteresis. Local curvature suggests higher stress level on package scale than on panel scale.